Post-Media poetics in a digital composite: The Oriental Dancer - Abdelmessih, Marie Therese (SOLETRAS, 2023)
The article addresses deep remixability in dance, film, software, media, and metafiction in The oriental dancer, a digital project composited by Sadim Mansour-Rondeau. The objective is to contest former anthropocentric constructs pertaining to dance and aesthetics. Attention is given to technical inventiveness and creativity of the digital creations, in the framework of Deleuzian-Guattarian and Derridean notions, together with post-media and software studies. It interrogates the dynamicity of the combinations or assemblages in the project’s composites to identify processes of deploying software for apprehending what escapes recognition. The concluding results stipulate the importance of appreciating digital composites as productive of sensations, affect, and forces, in a Deleuzian-Guattarian sense. This reiterates the dynamicity of software as a non-human agency that transpose multiple content, along with realities that intensify experience, thereby promoting various modes of seeing and being (Manovich; Parikka). Basically, the encounter with the The oriental dancer digital composite activates a poetics of potentiality that releases infinite modes of becoming, a gateway to the possibilities of future reinvention.